EXISTENTIALISM AS A THEORY OF LEARNING - Karimov, Rakhmat (MMIT Proceedings, 2023)
The article examines the fundamental principles of existentialism, such as individuality, freedom, subjective experience, responsibility, and authenticity. It also discusses the practical significance of existentialism in education, including personalized approach, development of critical thinking, personal autonomy, search for meaning and values, and emotional intelligence. In conclusion, the article emphasizes the need for a balanced approach, combining existentialism with other educational methods to ensure comprehensive and effective learning